ANALYSIS OF THE FEASIBILITY AND PRACTICABILITY OF E-MODULE BASED ON GUIDED INQUIRY INTEGRATED WITH VIRTUAL LABORATORY ON MOMENTUM AND IMPULSE MATERIAL - Najla, Rahma Disa; Panggabean, Deo Demonta (UNIVERSITAS NEGERI MEDAN, 2024)
This study aims to analyze the feasibility and practicality of an electronic module on momentum and impulse material based on guided inquiry and integrated with virtual laboratory. This type of research is Research and Development (R&D) with the Analyze, Design, Develop, Implement and Evaluation (ADDIE) development method. The instruments used are in the form of assessment sheets by experts and teacher and student response questionnaires. This research was conducted at SMA Swasta Budi Agung Medan on class X students totaling 40 students. The validation results show that the module is very valid/very feasible with the average result of 4.28 by material expert, 4.61 by media expert and 4.44 by educational practitioner. In terms of feasibility, the results of student response questionnaires show that the module is in very good/very practical category with the average percentage 89.56% in small group and 91.90% in large group. Based on the result obtained, this module is suitable for used in the learning process or used independently by students.